Genome editing demonstrates that the −5 kb Nanog enhancer regulates Nanog expression by modulating RNAPII initiation and/or recruitment - Agrawal, Puja (J Biol Chem, 2020)
Transcriptional enhancers have been defined by their ability to operate independent of distance and orientation in plasmid-based reporter assays of gene expression. At present, histone marks are used to identify and define enhancers but do not consider the endogenous role of an enhancer in the context of native chromatin. We employed a combination of genomic editing, single cell analyses, and sequencing approaches to investigate a Nanog-associated cis-regulatory element, which has been reported by others to be either an alternative promoter or a super-enhancer. We first demonstrate both distance and orientation independence in native chromatin, eliminating the issues raised with plasmid-based approaches. We next demonstrate that the dominant super-enhancer modulates Nanog globally and operates by recruiting and/or initiating RNA Polymerase II. Our studies have important implications to how transcriptional enhancers are defined and how they regulate gene expression.